(untitled) (American Journal of Islam and Society, 1992)
This book is a focused study on the Muslims in Canada with special teference to Muslims in the pmvince of Alberta. The study is both quantitative (it consists of the qudonnaire responses of 115 participants in Alberta) and qualitative (it develops discussions relevant to Canadian Muslims in general). One of the aims of the study is to highlight the extreme diversity of Muslims in Canada while showing that all of them have something very basic in common: their Islamic ideals. This diversity is adequately illustrated by detailing their multiple ethnicities and home countries, their different occupations, and their internal variations in identifying with Islam. The study further emphasizes this diversity is being positively integrated into mainstream Canadian society, contributing to it while preserving certain special traits. The discussion of how Muslims in Alberta maintain extensive links With Muslim lands as regads trade and socioreligious and humanitarian concerns is especially impressive. This study is more descriptive than analytical. It does not answer the question of how integration is possible without losing the essence of Islam. In the brief conceptual framework, the dynamics between religion and ethnicity is not as clear, i.e., which subsumes the other? In general, the study is very helpful to those who do not know much about Muslims in Canada. It also raises points that can help Muslims better present themselves collectively.